The value of recognition of prior learning in enhancing access and redress in teacher education - Makhatsane, Makabelo Iketleng (University of the Free State, 2020)
The Recognition of Prior Learning (RPL) is regarded as a priority in the effort to redress the discrimination of the past. RPL assists individuals to return to education and work at the pace that is related to the learner. RPL plays a role in facilitating access in teacher education through experience. The literature has shown that RPL can build confidence for students through self-reflection on their own experiences, thus making them less anxious about embarking on future studies. In the light of the fact that the qualification, the National Professional Diploma in Education (NPDE) through which students received access to education through the application of RPL has been terminated, this study intended to explore the value of RPL in enhancing access and redress in teacher education. The study followed a mixed method approach. The quantitative approach used a self-constructed closed-item questionnaire, whilst the qualitative approach consisted out of semi-structured interviews. In this study, a sample of hundred (100) students who were enrolled for the NPDE, participated in the questionnaires and in the survey. These participants were selected using random sampling. I selected every second person on the list, irrespective of race, gender or status, until one hundred (100) persons were reached. Quantitative data was entered via Microsoft Excel for analysis and SPSS for reliability testing, the Cronbach alpha coefficient was found to be 0.784. The quantitative data was analysed using both descriptive and inferential statistics in which tables and percentage distributions were used, to display data. The main findings of this research suggested that RPL plays a very important role in enhancing access and redress in teacher education. Data from both the questionnaires as well as the interviews suggested that it was only through RPL that they were able to access Higher Education Institutions (HE). In this way, RPL redressed past injustices and brought about the transformation of education. However, what came out very strongly in this study was that the aim of RPL was to enhance access and redress past injustices could be severely jeopardised by financial constraints experienced by the participants. In some cases, the lack of funding resulted in the participants having to terminate their studies for at least a year, in order to accumulate finances. It is my view that the lack of finances could have or will negatively influence the vision of ensuring access and redress through RPL. It is against this background that, among others, I recommend that the government and institutions of higher learning look into a funding model for students that wish to enter teacher education through RPL.
Keywords: Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2020; Access; Redress; Transformation; Discrimination; Past injustices; Experience; Teacher education; Recognition of Prior Learning (RPL); National Professional Diploma in Education (NPDE); Higher Education (HE)